The Implementation of Repositioning Interventions to Prevent Pressure Ulcers in ICU Patients at Pandan Arang Regional Hospital, Boyolali - Almar'ah Uswatun Khasanah; Ida Nur Imamah; Panggah Widodo (Al-Hijrah Indonesia, 2026)
Background: Decubitus ulcers are tissue damage caused by prolonged pressure without position changes. To prevent this, both pharmacological and non-pharmacological interventions can be applied, including the use of anti-decubitus mattresses, massage, and repositioning or mobilization. Repositioning helps reduce pressure and friction on the skin, thus preventing pressure ulcers. Objective: To determine the effect of repositioning in preventing pressure ulcers in patients receiving care in the Intensive Care Unit (ICU) of Pandan Arang Regional Hospital Boyolali. Method: This study used a descriptive case study design. The intervention was conducted over four consecutive days, with repositioning performed three times daily for 15 minutes every two hours. The risk of pressure ulcers was assessed using the Braden Scale before and after the intervention. Results: After repositioning, the Braden score of Mr. J increased from 12 (high risk) to 14 (moderate risk), and Mrs. S from 13 (moderate risk) to 16 (low risk), indicating a decreased risk of pressure ulcers. Conclusion: There was a noticeable reduction in pressure ulcer risk in bedridden patients following repositioning. Therefore, repositioning can be considered an effective non-pharmacological technique to prevent pressure ulcers.